Growth and Development Responses of Soybean (Glycine max L.) Under Several Combinations of Inorganic and Organic Fertilizer - Netty Syam; Hidrawati Hidrawati; Suraedah Alimuddin; Syamsu Rijal (AGRIVITA, Journal of Agricultural Science, 2023)
One of familiar green soybean, edamame is a vegetable that popularly chosen by the richest consumer. The reducing inorganic fertilizers can be realized gradually by transforming the farming from conventional to organic. Related to transformation, we observed the suitable combination of inorganic and organic fertilizers for the edamame growth and production. By a randomized block design, seven combinations of inorganic fertilizers (150 kg/ha Urea, 150 kg/ha SP-36, 100 kg/ha KCl) and organic fertilizers (compost) were applied. Three repeatations was adopted for each treatment and 30 plants per plot was used. The analysis of variance and Tukey HSD at 5% error were chosen. Based on the result, the combination of inorganic fertilizers and compost effect four plant growth and development variables such as the plant height, the number of leaves, the number of productive branches, and the time to produce 50% of a flower. The application of inorganic fertilizers at 50% and 75% combined with compost 10 t/ha increased the plant height, the number of productive branches, and the number of leaves. The number of seeded pods and the pod weight are not affected by all combinations of treatments.